Healthcare resource utilisation and costs of agitation in people with dementia living in care homes in England - The Managing Agitation and Raising QUality of LifE in Dementia (MARQUE) study. - Monica Panca (PLoS ONE, 2019)
Background People with dementia living in care homes often experience clinically significant agitation; however, little is known about its economic impact. Objective To calculate the cost of agitation in people with dementia living in care homes. Methods We used the baseline data from 1,424 residents with dementia living in care homes (part of Managing Agitation and Raising QUality of lifE in dementia (MARQUE) study) that had Cohen-Mansfield Agitation Inventory (CMAI) scores recorded. We investigated the relationship between residents' health and social care costs and severity of agitation based on the CMAI total score. In addition, we assessed resource utilisation and compared costs of residents with and without clinically significant symptoms of agitation using the CMAI over and above the cost of the care home. Results Agitation defined by the CMAI was a significant predictor of costs. On average, a one-point increase in the CMAI will lead to a 0.5 percentage points (cost ratio 1.005, 95%CI 1.001 to 1.010) increase in the annual costs. The excess annual cost associated with agitation per resident with dementia was £1,125.35. This suggests that, on average, agitation accounts for 44% of the annual health and social care costs of dementia in people living in care homes. Conclusion Agitation in people with dementia living in care homes contributes significantly to the overall costs increasing as the level of agitation increases. Residents with the highest level of agitation cost nearly twice as much as those with the lowest levels of agitation, suggesting that effective strategies to reduce agitation are likely to be cost-effective in this setting.